NFIC suppressed the epithelial ovarian cancer via modulating the balance of PTEN/TGFβ1/EGR1/BRD4 and SP1/EZH2 induced Inhibition of TBX2/MMPs signaling - Yanan Ren; Ren Xu; Di Zhang; Luyang Su; Ying Jin; Na Li; Yazhuo Wang (Scientific Reports)
Abstract This study aims to explore the impact of NFIC and its regulated signaling factors on epithelial ovarian cancer, providing new insights for the treatment of ovarian epithelial cancer. Bioinformatics methods were applied to predict and analyze NFIC and its downstream signaling factors. In vivo experiments involved dividing 27 purchased female nude mice into three groups: NC group, NFIC-OE group, and NFIC-OE + TBX2-OE group, to observe tumor growth in each group. In vitro experiments involved dividing the human epithelial ovarian cancer cell line SKOV3, OVCAR-3 and A2780 into five groups with different stimuli, using Western blot to observe protein expression, CCK-8 assay to observe cell proliferation, scratch assay to observe cell migration, transwell assay to observe cell invasion, Annexin V/PI assay to study apoptosis and Co-Immunoprecipitation experiment were used to study NFIC action. Bioinformatics revealed that NFIC promotes PTEN and TGFβ1, with TGFβ1 promoting the expression of TBX3 and EGR1, which in turn inhibit TBX2. Additionally, TBX2 inhibits PTEN and promotes MMPs. BRD4 promotes H3K27AC, which leads to TGFβ1 expression, while H3K27me3 inhibits TGFβ1 expression. EZH2 promotes H3K27me3, thereby inhibiting TGFβ1 and TBX3, and SP1 promotes the action of EZH2. In vivo, NFIC alleviated ovarian epithelial cancer, while TBX2 inhibited the effect of NFIC. In vitro, NFIC inhibited the expression of TBX2, nucleus SP1, EZH2, and MMPs, and promoted the expression of PTEN, nucleus BRD4, TGFβ1, and TBX3; TBX2 promoted MMPs expression. NFIC inhibited the migration and proliferation of SKOV3 cells, while TBX2 promoted it; NFIC functioned through TGFβ1 and PTEN, and their inhibition promoted the migration and proliferation of SKOV3 cells. NFIC inhibits the progression of epithelial ovarian cancer by regulating the balance of PTEN/TGFβ1/EGR1/BRD4 and SP1/EZH2 to suppress the TBX2/MMPs signaling pathway.